Retrospective challenges to pre-exposure prophylaxis (PrEP) use among people living with HIV—A qualitative analysis using the COM-B framework - Carina Hörst; Hannah Kitt; Helen Corkin; Dolores Mullen; Ammi Shah; Adamma Aghaizu; Clare Humphreys; Tamara Djuretic (PLoS ONE, 2026)
Biomedical interventions to prevent transmission of Human Immunodeficiency Virus (HIV), such as pre-exposure prophylaxis (PrEP), are available in England for free at specialised sexual health services (SSHS). Yet the number of new HIV diagnoses made in England among people exposed to HIV through heterosexual sex and among people of Black ethnicity are increasing. Published research discusses the barriers and facilitators to PrEP among people not living with HIV. We add to this literature by qualitatively exploring the retrospective barriers and facilitators to PrEP use and HIV prevention more broadly among people who are living with HIV now. We interviewed 26 participants between March 2021 and July 2022 from across England with varying backgrounds. We used the COM-B model to systematically extract areas that can inform behaviour change. Capability barriers included gaps in HIV and PrEP knowledge and mental health issues. Opportunity barriers included not being identified as having a PrEP need by healthcare professionals, which then hindered participants to learn more about PrEP, communication gaps with sexual partners and perceptions of (in)accessibility of PrEP. Motivational barriers included a perception of low HIV risk and HIV/ PrEP self-relevance, PrEP stigma, having reservations about taking medications, and perceiving HIV campaigns as too selective regarding the populations they target. Knowledge about PrEP constituted a capability facilitator; and wanting to stay safe and take control of one’s health was a motivational facilitator. Our findings mirror those identified in research conducted with people not living with HIV, but we believe that particularly strong narratives for HIV prevention can arise from learning from people living with HIV. We suggest that structural changes are required to achieve a shift in how sex, HIV and PrEP are discussed societally, allowing for changes in individual and interpersonal behaviours and a sustained decrease in HIV transmission among all groups.